Immunomodulation by microfilaria and its implication in the immune reaction against different vaccine antigens (Research, Society and Development, 2022)
This study addresses the Mansonellas which are among the most common causes of blood parasites and are widely distributed throughout Africa and Latin America. Given this context, this work aims to discuss the immunomodulation produced by mansonellosis and its implication in the immune reaction against different vaccine antigens. In order to achieve this objective, a methodology was used for the bibliographic research with the help of the websites Biblioteca Virtual de Saúde, Scielo – Scientific Electronic Library Online, Lilacs – Centro Latino-Americano e do Caribe de Informação em Ciências da Saúde and NIH. -NCBI-Pubmed – National Center for Biotechnology Information – National Library of Medicine. The following descriptors were used on these sites: Filaria, Immunology, Mansonelas and Vaccine. Immunomodulation produced by filarial nematodes predisposes them to spread to other non-filarial antigens. Thus, filarial infection may have a profound implication in the immune reaction against other antigens, be they vaccines, environmental allergens or other infections. Thus, immunosuppression seems to be the key in chronic filarial infections, where different highly effective mechanisms are used by the parasites to promote their survival. As a result, these infections end up presenting an extremely relevant characteristic, which is their propensity to induce regulatory effects on a variety of immune responses, including responses to vaccines and other infectious agents.